2018
DOI: 10.1007/s13197-018-3303-y
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo cheese whey hydrolyzed with Alcalase as an antibrowning agent in minimally processed apple

Abstract: Buffalo whey was hydrolyzed with Alcalase for different times t (i = 0, 0.5, 1, 2, 3, 4 or 6 h) and the browning inhibition of minimally processed apples was investigated. The hydrolysis process was followed by determination of the degree of hydrolysis. In order to understand possible modes of action on the enzymatic browning, whey was submitted to the analysis of antioxidant activity (ABTS radical sequestration, Fe chelating activity and reducing power), reactivity with quinones and inhibitory activity on pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The presence of these two amino acid residues could be responsible for the positive results observed for both antioxidant and anti-tyrosinase activities [13, 42]. To this extent, it has been recently reported the possible applications of buffalo whey hydrolysed with Alcalase as a natural substitute for additives conventionally used in the control of enzymatic browning in foods [43]. Moreover, it has been reported that glutathione and some glutathione analogues promoted tyrosinase inactivation; in particular, the addition of the -CH 2 SH moiety significantly improved the inhibition activity over the parent molecule [44].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of these two amino acid residues could be responsible for the positive results observed for both antioxidant and anti-tyrosinase activities [13, 42]. To this extent, it has been recently reported the possible applications of buffalo whey hydrolysed with Alcalase as a natural substitute for additives conventionally used in the control of enzymatic browning in foods [43]. Moreover, it has been reported that glutathione and some glutathione analogues promoted tyrosinase inactivation; in particular, the addition of the -CH 2 SH moiety significantly improved the inhibition activity over the parent molecule [44].…”
Section: Resultsmentioning
confidence: 99%
“…Later, Alcalase was employed to hydrolyze buffalo whey. The hydrolysate was applied to apple, and it prevented apple browning [717]. Sheep plasma has also been hydrolyzed by Alcalase, the hydrolysate improved the color stability in mutton patties [718].…”
Section: Hydrolysis Of Proteins From Different Sourcesmentioning
confidence: 99%
“…Silva et al. (2018) have found that when the nonhydrolyzate whey and phosphate buffer were used in treatment of apples, BI values showed no significant difference during storage except nonhydrolyzed whey gave the highest BI at the end of the storage.…”
Section: Resultsmentioning
confidence: 99%
“…Potato ( Solanum tuberosum L.) tubers are widely produced (over 368 million tonnes (FAOSTAT, 2020) and consumed all over the world, which is an important source of energy and some nutrients (Jimenez, Rossi, & Sammán, 2015). Browning is a major problem in food processing (Silva, Correa, Kechinski, & Brandelli, 2018), after peeling, cutting, slicing, especially fresh‐cut fruit, and vegetable processing like potatoes (Gong et al., 2019). Consumer acceptance of these products can be affected by the color (Sulaiman, Soo, Farid, & Silva, 2015) and also indicates poor quality and economic losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation